Promotıng Multılıteracy Framework - Based Lesson Plan for Englısh Language Teachıng In Senıor Hıgh School - Ana Christanti; Muhammad Nawawi (Universitas Nahdatul Ulama Surabaya, 2020)
The objective of the research was to promote a new model of designing activities in the lesson plan of English teachers. The model was derived from the phases of the Multiliteracy pedagogical Framework. It was qualitative research with documentation techniques for collecting data. The source of data was the document of lesson plans made by teachers of English. The data was statements on teaching-learning activities in the lesson plans. The author identified the lesson plan of teachers from Al Islam senior high school in Krian, Sidoarjo. The activities statements were categorized using the four phases and cognitive process of the Multiliteracy Framework; Situated Practice (Experiencing), Overt Instruction (Conceptualizing), Critical Framing (Analysis), and Transformed Practice (Applying) promoted by Cope and Kalantzis with New London Group in 1996. The result showed that the teachers just included two phases; Situated Practice (Experiencing) and Overt Instruction (Conceptualizing), no Overt Instruction (Conceptualizing), Critical Framing (Analysis), and Transformed Practice (Applying) yet in their teaching-learning activities. The teachers should change the old phases in their lesson plan with the four phases of the framework to guide them in applying multiliteracy in English language teaching. The next researcher could focus on teachers’ knowledge or belief about the multiliteracy framework to assure the implementation